Embracing Online Learning: The Readiness and Perceived Challenges among Health Sciences Distance Learners - Ahmad Sharoni, Siti Khuzaimah; Seman, Nordianna; Razali, Nurhazirah; Zamri, Zufazlizan (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: The shifting of conventional to online learning is prominent in our millennial era. The online pedagogy is dynamic in creating knowledge and simultaneously engaging learners with experts beyond boundaries. Our study aims to determine the readiness of distance learners in embracing online learning and their perceived challenge in accomplishing their academic journey. Methods: We employed the quantitative study design with a cross-sectional survey and this study was conducted in a public university. The health sciences learners who are currently undertaking their distance learning program were recruited by convenience sampling (N=128). The Online Learning Readiness Scale (OLRS) was adopted with its internal consistency ranging from 0.77 to 0.95 for five dimensions of measure. Results: Our results indicate a high level of online learning readiness. In addition, the highest level of readiness in the dimension of computer/internet self-efficacy whereas the least level was the learners’ control. Sixty-eight percent of learners reported poor internet connectivity as the main challenge in online learning. Moreover, we found that gender, age, and the learners’ program were not the significant factors affecting learners’ online learning readiness (p>.05). Conclusion: Our study revealed a high extent of online learning readiness among distance learners that display constructive embracing of current educational technology. Nevertheless, considering the poor internet connection, communication infrastructure needs to be further developed to bridge the gap between millennial learners and the Internet of Things (IoT).